(untitled) (Research, Society and Development, 2022)
Objective: To identify, through literary evidence, the impact of the COVID-19 pandemic on the maternal health of pregnant women in Brazil. Methodology: This is an integrative review carried out in the electronic databases Lilacs, Pubmed and Scielo, using the following descriptors: "COVID-19", "SARS-CoV-2", "severe acute respiratory syndrome coronavirus" and " pregnancy”. Full texts, available in Portuguese, English or Spanish, published between January 2020 and June 2022 were included; studies that addressed factors related to obstetric outcomes of pregnant women infected with COVID-19 or characteristics of care for these pregnant women during the COVID-19 pandemic in Brazil. Results: Nine articles made up the final sample of this study. Most of the studies used the cohort study, presenting a moderate level of evidence (III). There was a high risk of cesarean deliveries, premature deliveries and higher rates of hospitalizations in intensive care units among pregnant women with COVID-19, highlighting the fact that the pandemic favored the deficit of prenatal consultations carried out in the routine in the Primary Health Care networks, causing low access to care for pregnant women due to the rapid spread of the virus. Conclusion: There were several unfavorable maternal outcomes in pregnant women infected with COVID-19 in Brazil, from the main factors associated with greater severity of the disease, as well as those associated with a greater risk of death, requiring more specialized care by health teams, in addition to more robust studies focusing on Brazil.